DAMPAK ADVISORY OPINION INTERNATIONAL COURT OF JUSTICE TERHADAP DINAMIKA KONFLIK BERSENJATA ISRAEL DAN PALESTINA - Surachman, Vitriyah Arafah; Susanti, Rahtami (The Juris, 2024)
The reaserch aims to analyze the legal considerations and the impact of advisory opinions issued by the International Court of Justice (ICJ) on the dynamics of the armed conflict between Israel and Palestine. The background of the conflict stems from the history of illegal occupation and human rights violations by Israel against Palestine which attracted international attention. This research uses a normative legal approach with historical and case methods to examine the implementation of international law related to the research. The research specification uses descriptive analytical with data collection techniques used, namely the literature study method. The results of the analysis show that the ICJ Advisory opinion is normatively non-binding, but has a significant impact in three main aspects. The political aspect, strengthening the Palestinian position in international forums and increasing political pressure from countries to Israel. The moral aspect, strengthening international support for Palestine to encourage a two-state solution. The legal aspect, emphasizing Israel's violations of international law, including the right to self-determination and urging an immediate end to the occupation and illegal practices. The implementation of the Advisory opinion ICJ has major challenges, mainly due to Israeli resistance and the lack of effective enforcement mechanisms. The study underscores the importance of the ICJ's role in implementing a more effective rule of international law and the strategic steps needed to realize a two-state solution.